Early recovery after impacted mandibular third molar surgery with Blue M healing gel - Le, Nguyen Thi My; Ngan, Phan Thuy; Huy, Ly Gia; Hau, Nguyen Cong; Tram, Vu Thi Ngoc; Nam, Nguyen Hoang (Tạp chí Nghiên cứu Y học, 2026)
Impacted mandibular third molar surgery is commonly followed by pain, facial swelling, trismus, and delayed soft-tissue healing, which can affect patient comfort and oral function. This controlled clinical interventional study with longitudinal follow-up evaluated Blue M gel as an adjunctive local therapy after impacted mandibular third molar removal. Eighty-six eligible patients were randomly assigned to the Blue M gel group or the control group, with 43 patients in each group. Baseline demographic, clinical, and tooth-related characteristics were comparable. Postoperative outcomes included facial swelling, pain, trismus, gingival coverage of the extraction socket, and early wound healing. Both groups showed gradual reduction in swelling over time, but the Blue M gel group had significantly less postoperative swelling after adjustment. Pain scores were also significantly lower in the Blue M gel group from day 1 to day 7. No significant between-group difference was observed for trismus. At day 7, the Blue M gel group showed better gingival coverage of the extraction socket and more favorable wound healing (OR = 5.22 [95% CI: 1.57 - 17.43], p < 0.001) than the control group. These findings suggest that Blue M gel may improve early postoperative recovery after impacted mandibular third molar surgery, particularly by reducing swelling and pain and enhancing gingival coverage and soft-tissue healing.